Fenomena Gegar Budaya pada Warga Negara Perancis yang Bekerja di Jakarta - Yusnia Khoirunnisa; Nathalia Perdhani Soemantri (Universitas Andalas, 2019)
The cultural shock will be increasingly visible if the newcomer has a cultural origin that is far different from the new culture he is attending. This study aims to see how the phenomenon of culture shock that occurs in French citizens who work in Jakarta. The concept used as a knife of analysis in this study is the concept of Cultural Communication and Cultural Concentration, which includes stages, phases, and forms of Cultural Concussion. The method of this research is using descriptive qualitative with the main data collection obtained from the results of interviews with three French citizens who work in Jakarta. The results showed that the three French citizens experienced a cultural shock in the form of language, food, weather, attitude, order. The cultural shock reactions experienced by them are feeling confused, stressed, homesick, physically ill, and always compare everything with their home country. The stages of cultural shock experienced by French citizens, namely the phase of excitement, the phase of disappointment, the initial phase of resolution and the phase function effectively.